Synthesis and investigation of a high-activity catalyst: Au nanoparticles modified metalic Ti microrods for NaBH4 electrooxidation. (15th February 2018) - Song, Congying; Li, Biaopeng; Cheng, Kui; Ye, Ke; Zhu, Kai; Cao, Dianxue; Wang, Guiling
Abstract: A novel catalyst electrode of Au nanoparticles modified Ti microrods is synthesized through a route of hydrothermal etching and electrodeposition. As substrate, the metallic Ti microrods are in-situ etched from the Ti plate using hydrochloric acid as an etching reagent. After that, Au is prepared on the metallic Ti microrods in a form of nanoparticle by electrodeposition. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) are conducted to investigate the structure and phase composition of the Au nanoparticles modified Ti microrods (Au/Ti MRs) electrode. Besides, the electrocatalytic property of the Au/Ti MRs electrode for NaBH4 oxidation is explored through chronoamperometry (CA) and cyclic voltammetry (CV). In alkaline solution, the Au/Ti MRs electrode displays excellent electrocatalytic property and good stability. At 0 V, there is a current density of 12.12 mA cm −2 on the as-prepared electrode in 2 mol L −1 NaOH and 0.1 mol L −1 NaBH4 that is twice as the current density on Au nanoparticles modified Ti plate electrode demonstrating huge potential for application in direct borohydride fuel cell. Graphical abstract: Highlights: Metallic Ti MRs substrate is obtained by hydrothermal etching. Au/Ti MRs reveal good catalytic activity and stability toward NaBH4 oxidation. Au/Ti MRs possess special 3D structure and large surface area.